Staging a performance Australian drama series - Russell, Geoff; Video Education Australasia (Bendigo, Vic.: Video Education Australasia, 1993)
This program examines the staging and management of a professional production by Barnstorm theatre at Melbourne's St. Martin's Youth Arts Centre
Executive producer, Neil Barrett
Keywords: Theatre -- Australia